Pharmacist intervention in cardiovascular disease prevention: lipid modifying treatment optimisation in type 2 diabetes within hastings primary care network. (30th November 2022) - Kong, H Y; Purdy, S; Fox, D; Patel, P; Bandobranski, S; Syed, H
Abstract: Introduction: Cardiovascular disease (CVD) leads to 1 in 4 premature deaths with higher likelihood in the most deprived population 1 . Consistent data demonstrated efficacy of statins in CVD prevention and mortality reduction through modifying lipid profile 1, 2 . NICE:CG181 recommends high-intensity statin, namely atorvastatin 20mg daily in type 2 diabetes (T2DM) with high risk of developing CVD 1, whilst the European Society of Cardiology suggests LDL-C target below 1.4mmol/L, the lower the better 2 . In contrast, 30% of patients in Hastings Primary Care Network (PCN) are prescribed sub-optimal statin therapy 3 with scope to promote medicine optimisation through modification of CVD risk factor in one of the England's most deprived areas. Aim: Lowering patient's CVD risk through optimising statin therapy and improving practice's compliance with NICE:CG181. Methods: NHS Health Research Authority Decision tool was followed, ethics approval was not required. Statin prescribing data were obtained through OpenPrescribing database. This pilot study focused on the prescribing of simvastatin at one surgery within the PCN where patients were identified using the surgery medical information system with the inclusion clinical codes of: "T2DM", "QRISK2>10%", "latest LDL-C>1.4mmol/L" and "current simvastatin 10/20/40mg prescription". Systematic review of patient medical records was followed, including medical history, latest lipid profile and liver function, allergies, history of statin intolerance, previous lipid therapy and frailty status determined using the electronic frailty index, Rockwood score and medical notes. Patients with heterozygous familial hypercholesterolaemia diagnosis, confirmed statin intolerance and moderately-to-severely frail were excluded. Patients were contacted to exercise shared decision-making. Once intervention agreed, prescription was initiated for prescriber authorisation. Blood test 3 months post-intervention monitored for liver function and lipid profile. Results: Search in February 2022 identified 44 patients with 39 suitable for intervention after exclusion. Thirty-six contactable patients were all switched to high-intensity statin. Thirty-four were switched to atorvastatin 20 mg whilst two with prior atorvastatin intolerance were switched to rosuvastatin 10 mg. At baseline, 32 patients (88%) had cholesterol profile done within a year as per NICE:CG181. Three-month post-intervention blood tests were completed for 21, with 15 pending; 33% (7/21) had a reduction of LDL-C. In February 2022, 28.9% of the practice's statin prescriptions were of low and medium intensity and was reduced to 25.6% post intervention. Discussion/Conclusion: All contactable patients had statin therapy optimised after exercising shared decision-making with improvement of prescribing compliance to NICE:CG181 demonstrated in this practice. Findings were inconclusive whether the intensification of statin therapy demonstrated cholesterol lowering effect in this cohort. Study limitations due to small sample size, currency of baseline profile at time of intervention and patient compliance not measured. Raised LDL-C observed could have been influenced by lifestyle changes such as poor diet and lack of exercise 1 . The limitations of this study will be reviewed for future roll out across Hastings PCN. Further exploration of therapy compliance, lifestyle education and the barriers to regular blood test would facilitate such medicine optimisation intervention. In conclusion, patients prescribed with sub-optimal lipid therapy should be reviewed and managed through healthy lifestyle recommendations and aggressive pharmacological intervention. References: 1. National Institute for Health and Care Excellence. Cardiovascular disease: risk assessment and reduction, including lipid modification, CG181. 2016 [cited 2022 Jul 27]. Available from: https://www.nice.org.uk/guidance/cg181 2. Mach F, Baigent C, Catapano AL, Konskinas CK, Casula M, Badimon L, et al. 2019 ESC/EAS Guidelines for the management of dyslipidaemias: lipid modification to reduce cardiovascular risk: the task force for the management of dyslipidaemias of the European Society of Cardiology (ESC) and European Atherosclerosis Society (EAS). Eur Heart J [Internet]. 2019 Aug [cited 2022 Jul 27]. Available from: https://academic.oup.com/eurheartj/article/41/1/111/5556353#207091308 DOI: 10.1093/eurheartj/ehz455 3. OpenPrescribing.net. Bennett Institute for Applied Data Science. University of Oxford. [Internet]. 2022 [cited 2022 Jul 30]. Available from: https://openprescribing.net/measure/statinintensity/pcn/U99438/